A critical analysis of weld heat input measurement through a water-cooled stationary anode calorimeter. (3rd July 2016) - Hurtig, K.; Choquet, I.; Scotti, A.; Svensson, L.-E.
Abstract : Comprehensive models of heat transfer require specification of the total amount of heat received by the workpiece. The objective of this work was to critically examine the use of a water-cooled stationary anode calorimeter to obtain both arc efficiency and total heat input into the workpiece. For simplicity and clarity, this last quantity is called the gross heat input. The effects of current, material type and water flow rate on the calorimeter performance were determined experimentally. Some measures for reducing errors in calorimetry were evaluated. Improvements were made to reduce heat losses from the top surface of the test coupon and boost heat removal from the opposite surface. A sensitivity test was conducted to estimate the effect of measurement inaccuracies. The results demonstrate the effectiveness of calorimetry for measuring gross heat input in arc welding.